Kolokium Kaunseling Kebangsaan 2016 - Amalia, Madihie (2016)
Kolokium Kaunseling Kebangsaan 2016 was held on 28th April 2016 organized by Persatuan Kaunseling Malaysia Antarabangsa (PERKAMA International) at the Ministry of Tourism & Culture Malaysia.